2013
DOI: 10.1590/s1413-70542013000500002
|View full text |Cite
|
Sign up to set email alerts
|

Competitive ability of black common bean genotypes with weeds

Abstract: The morpho-physiologic characteristics of common bean plants can affect their competitive ability with weeds. The objective of this work was to evaluate the competitive ability of black bean genotypes with weeds. An experiment was carried out in the 2010/ 11 cropping season in Papanduva, SC, southern Brazil, in order to verify the variability of some plant characteristics among genotypes of common bean. The randomized block design was used, with four replications. Seven cultivars underwent the treatments: BRS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Aguyoh & Masiunas (2003) reported that snap bean yield was reduced by 13%-58% at densities 0.5-8 of redroot pigweed plants per meter, respectively. Vogt et al (2013) reported that the losses of grain yield in black common bean genotypes due to weed interference ranged from 30.8% to 54.9%.…”
Section: Pod and Seed Yieldmentioning
confidence: 99%
“…Aguyoh & Masiunas (2003) reported that snap bean yield was reduced by 13%-58% at densities 0.5-8 of redroot pigweed plants per meter, respectively. Vogt et al (2013) reported that the losses of grain yield in black common bean genotypes due to weed interference ranged from 30.8% to 54.9%.…”
Section: Pod and Seed Yieldmentioning
confidence: 99%
“…The carioca and black common bean group are the two most consumed types in Brazil (Vogt et al, 2013), cultivated mainly by small holder farmers.…”
Section: Introductionmentioning
confidence: 99%
“…Carioca and Preto beans correspond to around 85% of the Brazilian bean market (Ribeiro et al, 2014). Other types of beans are important regional foods, including the Fradinho bean (cowpea), which is popular in Northeastern Brazil, representing approximately 10% of the total Brazilian dry bean market (Vogt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%